1996
DOI: 10.1046/j.1365-2141.1996.d01-1794.x
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of red cells in narrow tubes in vitro as a model of the microcirculation

Abstract: To investigate the behaviour of red cells in the microcirculation, we established a new capillary method using narrow fluorinated ethylenepropylene copolymer tubes with internal diameters of 12.5 and 25.0 microns. Red cell flow in the tubes under a given range of pressure was analysed through a video system connected to a microscope. The experimental condition was adjusted so that the velocity of the control normocytes would be compatible with that in corresponding vessels in vivo, 0.5-1.5 mm/s. In the 12.5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…A pressure-driven pump system with a flow controller (Fluigent, Villejuif, France) was used to pump each solution through the microfluidic device at a physiologically relevant average velocity of 1 mm/s (44)(45)(46)(47). This velocity corresponds to a volumetric flow rate of 0.24 mL/min and an apparent wall shear rate of 61 s À1 for our channel dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…A pressure-driven pump system with a flow controller (Fluigent, Villejuif, France) was used to pump each solution through the microfluidic device at a physiologically relevant average velocity of 1 mm/s (44)(45)(46)(47). This velocity corresponds to a volumetric flow rate of 0.24 mL/min and an apparent wall shear rate of 61 s À1 for our channel dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…11 As for plaque disruption, the cardiac events that occurred during bathing in group A seemed to show that the drastic hemodynamic change triggered this. Some reports, referring to thrombosis, have indicated that decreased fibrinolytic activity and platelet hyperaggregability, caused by the hyperthermal stress of bathing, activates blood hyperviscosity, 12,13 and as for vasoconstriction, Tanabe et al suggested that for patients with MI the physical stress caused by bathing seems to bring about coronary artery spasm, a speculation derived from the number of transient ischemic ST-T changes observed with ECG monitoring during bathing. 14 According to these reports, bathing in patients with MI may trigger coronary thrombosis because it causes vasospasm, leading to endothelial impairment of the coronary artery, which results in plaque disruption, while simultaneously, the hyperthermal from bathing activates platelet function and inactivates the fibrinolytic system.…”
Section: Discussionmentioning
confidence: 99%
“…Possible pathomechanisms can be more or less direct. A direct mechanism would be associated with a hindered flow of larger, less flexible erythrocytes through microcirculation, which is a phenomenon that might contribute to myocardial ischemia [23,24]. Patients with high MCV commonly develop hyperhomocysteinemia [25], which is known to augment cardiovascular risk [26][27][28].…”
Section: Discussionmentioning
confidence: 99%